ANALISIS KETELITIAN GEOMETRIK CITRA SATELIT PLEIADES 1B DAN SPOT 6 UNTUK PEMBUATAN PETA DESA - Sukojo, Bangun Muljo; Nurwauziyah, Iva (Departemen Teknik Geomatika ITS, 2018)
In this study, Pleiades 1B and SPOT- 6 images can be reviewed the extent to which the geometric accuracy of the actual conditions that will be used as source data for making village map with a large scale. In research conducted process of rectification by using data of ground control points (GCP) on the satellite image Pleiades-1B and SPOT 6, which using two methods, namely polynomial order 1 and order 2, then test the accuracy of geometric on the results of rectification the image to determine the level of precision horizontal based on Perka BIG No. 15 of 2014, so be analyzed the accuracy of horizontal imagery for making village map. The results obtained from the process of image rectificaation with 8 GCP, RMS value obtained method of polynomial 2nd orde is better than 1st orde, i.e. 0,188 pixel on the Pleiades 1B image and 0,350 pixel on the SPOT 6 image. Based on geometric accuracy testing obtained value of RMSE on the Pleiades 1B image is 0,801 meters and on the SPOT 6 imaage is 2,489 meters on the image of the results of the polynomial 1st order rectification method and on the polynomial 2nd order rectification method, RMSE values obtained for the image of the Pleiades 1B is 0,647 meters and 2,386 meter for the SPOT 6. For the feasibility of high-resolution imagery for creating village maps based on Technical Specifications Mapping Village 2016 by BIG, Pleiades 1B image eligible cartography village with a scale of 1: 2500, 1: 5000, 1: 10.000, while on satellite images SPOT 6 meet requirements for the manufacture of a village map with a scale of 1: 10,000.